2019
DOI: 10.3390/ijerph16193592
|View full text |Cite
|
Sign up to set email alerts
|

Does the New Rural Pension System Promote Farmland Transfer in the Context of Aging in Rural China: Evidence from the CHARLS

Abstract: The lack or instability of the pension system for the elderly in rural China has become a paramount obstacle for sustainable land transfer, namely land use right transfer among farmers, in the context of aging. The New Rural Pension System (NRPS), a pilot project that provided basic security for the elderly, was implemented in 10% of counties in 2009 and rapidly promoted nationwide in China. This study evaluates the impact of NRPS on farmland transfer by developing econometric models by employing the China Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 30 publications
2
14
1
Order By: Relevance
“…From the perspective of land transfer, land endowment significantly impacts the land transfer decision, especially when the head of a household is older and thus more inclined to transfer land. This result is consistent with the findings of He et al [36], who argued that land transfer can liberate the rural elderly from the heavy burden of traditional farming [6]. More specifically, with the increase of age, the income of famers through farming gradually decreases, while the rent obtained from land transfer can bring them higher income.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…From the perspective of land transfer, land endowment significantly impacts the land transfer decision, especially when the head of a household is older and thus more inclined to transfer land. This result is consistent with the findings of He et al [36], who argued that land transfer can liberate the rural elderly from the heavy burden of traditional farming [6]. More specifically, with the increase of age, the income of famers through farming gradually decreases, while the rent obtained from land transfer can bring them higher income.…”
Section: Discussionsupporting
confidence: 92%
“…The extensive operation of traditional agriculture causes an increasing proportion of the rural population to move to neighboring towns or cities, which leads to an increase in the land abandonment rate year by year in rural areas, especially in remote mountainous areas or backward areas [1,2]. Land circulation can effectively alleviate the problem of land abandonment, increase efficiency of land use and ecological security, optimize the distribution of elements, marginal output level, and income poverty reduction triple effect [3][4][5][6], and realize land scale management, solving food security and quality control problems in developing countries [7]. For instance, Brauw et al [8] reported that land transfer improves the mobility of Ethiopian farming households, thus increasing their incomes.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of health, the rates of chronic diseases and overweight rose over the 2011–2015 period by 8.6 and 6.0 pp, respectively, although physical and social activity also increased by 3 and 2.5 pp and the prevalence of smoking declined by 2.8 pp. Additionally, as in previous studies using the CHARLS data [ 31 , 75 , 76 , 77 ], the rate of pension coverage increased sharply from 44% in 2011 to 74% in 2015. The translog household expenditure per capita also significantly rose from 8.6 to 9.1 during the same period.…”
Section: Resultssupporting
confidence: 74%
“…Thus, a series of policies have been issued to promote farmland transfer. According to the data of the Ministry of Agriculture of the People's Republic of China, the transferred area of farmland reached 2.69 × 10 7 hm 2 by the end of 2018, accounting for 30.4% of the total area of household-contracted farmland, approximately 20% higher than in 2012 [13], and a more important reason for farmland transfer flourishing in China is that the government expected to promote rural households' income through farmland transfer [14]. Because the income gap between urban and rural is the important cause of the large population migration in rural China, which further caused "hollowing village" and the countryside decline [15][16][17].…”
Section: Introductionmentioning
confidence: 99%